Serum Dechlorane Plus (DPs) levels in thyroid disease patients: Influence of gender, age, and metastasis - Ye Wu; Yuhao Fan; Xinyu Lou; Dan Chen; Jun jin; Ying Wang; Ting Yang; Zhiyan Liu (Ecotoxicology and Environmental Safety)
The study revealed that the serum DPs concentrations in thyroid patients ranged from 2.45 to 141.25 ng/g lw, with the female group showing higher DPs concentrations and a higher fanti value than males. Younger participants exhibited had higher serum DPs concentrations and fanti values compared to older age groups, compared to middle-aged and elderly groups, indicating a tendency for anti-DP accumulation. In addition, the fanti value was found to be lower in patients with metastatic thyroid tumor, potentially due to an enhanced capacity to metabolize anti-DP post-metastasis. We also examined the population of patients with varying diameters. Consequently, future studies should further investigate the possible relationship between DPs and thyroid function, with an emphasis on anti-DP.